Increasing the color quality of the 7000K conformal packaging MCW-LEDs by varied red-emitting K2SiF6:Mn4+ conversion phosphor's size. Issue 1 (1st January 2017) - Tin, Phu Tran; Nhan, Nguyen Huu Khanh; Quang Minh, Tran Hoang
Abstract: Phosphor-converted white light-emitting diodes (pc-WLEDs) are energy efficient and environmentally friendly light sources with a long lifetime, applicable in both display backlights and general lighting. In this research, we investigated the influence of the red-emitting K2 SiF6 :Mn 4+ conversion phosphor on the color quality of the 7000K conformal packaging multi-chip white LEDs (MCW-LEDs). The effect of the red-emitting Ba2 Si5 N8 Eu 2+ convention phosphor is demonstrated based on Mie Theory by Mat Lab and Light Tools software. The research results indicated that the color quality of MCW-LEDs was crucially affected by the red-emitting K2 SiF6 :Mn 4+ conversion phosphor's size. This research demonstrated a significant recommendation for selecting and developing the phosphor materials for MCW-LEDs manufacturing.